Novel highly emissive non proteinogenic amino acids : synthesis of 1,3,4-thiadiazolyl asparagines and evaluation as fluorimetric chemosensors for biologically relevant transition metal cations - Esteves, Cátia I. C. (2011)
Highly emissive heterocyclic asparagine derivatives bearing a 1,3,4-thiadiazolyl unit at the side chain, functionalised with electron donor or acceptor groups, were synthesised and evaluated as amino acid based fluorimetric chemosensors for metal cations such as Cu2+, Zn2+, Co2+ and Ni2+. The results suggest that there is a strong interaction through the donor heteroatoms at the side chain of the various asparagine derivatives, with high sensitivity towards Cu2+ in a ligand-metal complex with 1:2 stoichiometry. Association constants and detection limits for Cu2+ were calculated. The photophysical and metal ion sensing properties of these asparagine derivatives confirm their potential as fluorimetric chemosensors and suggest that they can be suitable for incorporation into chemosensory peptidic frameworks.